Atomic Layers of MoO2 with Exposed High‐Energy (010) Facets for Efficient Oxygen Reduction. Issue 13 (6th February 2018) - Zhang, Chao; Zou, Xiaolong; Du, Zhiguo; Gu, Jianan; Li, Songmei; Li, Bin; Yang, Shubin
Abstract: Although 2D nanocrystals with exposed high‐energy facets are highly desired in the field of catalysts due to their anticipant high catalytic activities, they are difficult to be gained. Here, atomic layers of metallic molybdenum dioxide (MoO2 ) with primarily exposed high‐energy (010) facet are achieved via a facile carbothermic reduction approach. The resultant MoO2 exhibits single‐crystalline, monoclinic, and ultrathin features with nearly 100% exposed (010) facet, which can significantly reduce reaction barriers toward the oxygen reduction reaction. As a consequence, the atomic layers of MoO2 exhibit high electrocatalytic activity, excellent tolerance to methanol, and good stability for the oxygen reduction reaction in alkaline electrolyte, superior to commercial Pt/C catalysts. It is believed that such new transition metal oxide catalysts with exposed high‐energy facets have broad applications in the areas of energy storage and conversions. Abstract : Atomic layers of molybdenum dioxide (MoO2 ) with exposed high‐energy (010) facets are achieved via a carbothermic reduction approach. The resultant MoO2 exhibits single‐crystalline features with nearly 100% exposed (010) facet, which can significantly reduce reaction barriers towards the oxygen reduction reaction. The as‐prepared MoO2 exhibits high electrocatalytic activity and good stability for the oxygen reduction reaction, superior to commercial Pt/C catalysts.